Formulation and Viability of Consortia LIBeM Using Protective Agent Skim Milk Subjected to Freeze Drying Method for Degradation of Oil Sludge Contaminated Soil (Journal of Environmental Microbiology and Toxicology, 2019)
The formulation and viability of locally-isolated beneficial microorganisms (LIBeM) consortia was conducted by using protective agent skim milk at 30% (w/v). A 10% (v/v) of inoculum consists of mixed cultures C. tropicalis-RETL-Cr1+ C. violaceum-MAB-Cr1 + P. aeruginosa-BAS-Cr1 (RETL-Cr1+ MAB-Cr1+BAS-Cr1) were obtained from the Environmental Microbiology Laboratory, Universiti Malaysia Sabah and tested for biodegradation of oil sludge using the live cell powdered form. LIBeM formulation was carried out by using lyophilization under vacuum conditions for 24 hours. The viability of the initial cell loads on the final recovery after freeze drying process was measured weekly by heterotrophic plate counts (HPC). Surface morphological of LIBeM powder (LiBeM-POW) was observed under scanning electron microscopy (SEM) to show any changes on the surface cell structures. The results showed that the use of 10% (v/v) of inoculum with 108 CFU/ mL as initial cell concentrations and 30% (w/v) skim milk as protective agent yielded 31.9% maximum viability. The findings also indicate that the survival rate of LIBeM cells have potential to survive and functionality even after 13 weeks of the storage with 106 CFU/ mL recorded. The effectiveness of microbial formulation of LiBeM-POW was done by carrying out the biodegradation experiment in ASP-bioreactor system for 56 days. Two sets of ASP- bioreactor system containing 2 kg of soil mixed with 20% (v/v) of oil sludge were prepared as T1: treatment with consortia LIBeM-POW and T2: natural attenuation as a control plot. The results indicated that LIBeM-POW has potential to be applied in bioremediation of oil sludge contaminated environments with 92% degradation of TPH as compared to natural attenuation 26% degradation. This finding suggests the possibility of producing freeze dried powder of LIBeM consortia with high viability for prior used in bioremediation study. The comparison of other protective agent used by previous studied was also discussed in this paper.
Keywords: LIBeM Consortium freeze drying; viability; survival rates; biodegradation; oil sludge